Bail in Lithuania’s Criminal Law - Bagdžius, Justinas (Teisė, 2019)
The article presents a historical analysis of the release from criminal liability on bail set forth in the Criminal Code of Republic of Lithuania, trying to understand the reasons of its establishment and formation in Lithuania’s Criminal Law. The origins of the surety for perpetrators are sought even in the early ages law of the state of Lithuania.